Perkembangan FinTech Terhadap Crowdfunding dan Blockchain di Indonesia - Oky Wida Syahputra; Shasi Naila Zahra Kamila; Sahwan Sakha Salladin; Maliana Puspa Arum (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Fintech is recognized as a crucial innovation in the financial industry and is growing rapidly in Indonesia, driven by the sharing economy, regulations, and information technology. Financial technology transforms the way financial services are accessed and managed, providing efficient solutions. Crowdfunding plays a vital role in supporting initiatives with online contributions. Blockchain, a distributed ledger technology, offers high security and transparency. This research employs a descriptive-analytical approach to investigate fintech development in Indonesia, highlighting growth, innovation, and blockchain implementation. From this research, the authors conclude that the development of Fintech in Indonesia, particularly in Crowdfunding and Blockchain, has a positive impact on the accessibility of financial services, investment innovation, and the prevention of accounting fraud, forming a solid foundation for sustainable growth in the modern financial ecosystem.